How civil wars start and how to stop them - Walter, Barbara F. (Crown, 2022)
Political violence rips apart several towns in southwest Texas. A far-right militia plots to kidnap the governor of Michigan and try her for treason. An armed mob of Trump supporters and conspiracy theorists storms the U.S. Capitol. Are these isolated incidents? Or is this the start of something bigger? Barbara F. Walter has spent her career studying civil conflict in places like Iraq and Sri Lanka, but now she has become increasingly worried about her own country. Perhaps surprisingly, both autocracies and healthy democracies are largely immune from civil war; it’s the countries in the middle ground that are most vulnerable. And this is where more and more countries, including the United States, are finding themselves today. Over the last two decades, the number of active civil wars around the world has almost doubled. Walter reveals the warning signs—where wars tend to start, who initiates them, what triggers them—and why some countries tip over into conflict while others remain stable. Drawing on the latest international research and lessons from over twenty countries, Walter identifies the crucial risk factors, from democratic backsliding to factionalization and the politics of resentment. A civil war today won’t look like America in the 1860s, Russia in the 1920s, or Spain in the 1930s. It will begin with sporadic acts of violence and terror, accelerated by social media. It will sneak up on us and leave us wondering how we could have been so blind. In this urgent and insightful book, Walter redefines civil war for a new age, providing the framework we need to confront the danger we now face—and the knowledge to stop it before it’s too late.